2007
DOI: 10.1038/sj.jid.5700823
|View full text |Cite
|
Sign up to set email alerts
|

Hair Follicle Regeneration Using Grafted Rodent and Human Cells

Abstract: Hair follicle regeneration involves epithelial-mesenchymal interactions (EMIs) of follicular epithelial and dermal papilla (DP) cells. Co-grafting of those cellular components from mice allows complete hair reconstitution. However, regeneration of human hair in a similar manner has not been reported. Here, we investigated the possibility of cell-based hair generation from human cells. We found that DP-enriched cells (DPE) are more critical than epidermal cells in murine hair reconstitution on a cell number bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
90
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(92 citation statements)
references
References 45 publications
1
90
0
1
Order By: Relevance
“…6B), confirming the known requirement for dermal cells (Ehama et al, 2007). Conversely, when Sox2GFP dermis was engrafted without epithelial cells, a few hairs formed, indicating low-level contamination of dermal cells with epidermal cells (Fig.…”
Section: Sox2-positive Dermal Papilla Cells Are Required For Formatiosupporting
confidence: 67%
See 2 more Smart Citations
“…6B), confirming the known requirement for dermal cells (Ehama et al, 2007). Conversely, when Sox2GFP dermis was engrafted without epithelial cells, a few hairs formed, indicating low-level contamination of dermal cells with epidermal cells (Fig.…”
Section: Sox2-positive Dermal Papilla Cells Are Required For Formatiosupporting
confidence: 67%
“…Grafting studies were performed as previously described (Ehama et al, 2007), except for the following modifications. On the first day of the procedure, 6-mm diameter chambers (Renner, Dannstadt, Germany, Cat.…”
Section: Epidermal-dermal Reconstitution In Graft Chambersmentioning
confidence: 99%
See 1 more Smart Citation
“…6 These observations confirm that low passages of cultured DPCs with aggregative growth not only have the ability to induce complete regeneration of hair follicles, but also carry the information needed to determine the nature of the hair, as corroborated by subsequent research. 7,8 It should be emphasized that the ability of DPCs to induce HF formation is dependent on their aggregative growth. But the mechanism by which the aggregative behavior disappears is not yet clear.…”
mentioning
confidence: 99%
“…The most accessible source of human skin is neonatal foreskin. Early studies demonstrated that, although the foreskin epidermis is able to form HFs in combination with a murine DP, the foreskin dermis lacks the necessary cell populations or signals (24). Until recently, only fetal dermal and epidermal cells from the second trimester were known to generate hair follicles (18).…”
mentioning
confidence: 99%